Money laundering compliance - Bennett, Tim (Bloomsbury Professional, 2014)
Money Laundering Compliance, 3rd edition provides a technical and practical overview of both the UK and international provisions designed to prevent the laundering of the proceeds of serious crime, and the financing of terrorism.Money laundering has continued to grow over recent years approaching £80 billion in the UK alone, and USD 3 trillion per year globally. Money Laundering Compliance, 3rd edition provides a technical and practical overview of both the UK and the international provisions designed to prevent the laundering of the proceeds of serious crime, and the financing of terrorism.